The potential contribution of geothermal energy to electricity supply in Saudi Arabia. Issue 9 (20th October 2016) - Chandrasekharam, D.; Lashin, Aref; Al Arifi, Nassir
Abstract : With increase in demand for electricity at 7.5% per year, the major concern of Saudi Arabia is the amount of CO2 being emitted. The country has the potential of generating 200×10 6 kWh from hydrothermal sources and 120×10 6 terawatt hour from Enhanced Geothermal System (EGS) sources. In addition to electricity generation and desalination, the country has substantial source for direct application such as space cooling and heating, a sector that consumes 80% of the electricity generated from fossil fuels. Geothermal energy can offset easily 17 million kWh of electricity that is being used for desalination. At least a part of 181, 000 Gg of CO2 emitted by conventional space cooling units can also be mitigated through ground-source heat pump technology immediately. Future development of EGS sources together with the wet geothermal systems will make the country stronger in terms of oil reserves saved and increase in exports.